Apoptosis and genes involved in oral cancer - a comprehensive review - Ruby Dwivedi; Rahul Pandey; Shaleen Chandra; Divya Mehrotra (Frontiers Media S.A., 2020)
Oral cancers needs relentless research due to high mortality and morbidity associated with it. Despite of the comparable ease in accessibility to these sites, more than 2/3rd cases are diagnosed in advanced stages. Molecular/genetic studies augment clinical assessment, classification and prediction of malignant potential of oral lesions, thereby reducing its incidence and increasing the scope for early diagnosis and treatment of oral cancers. Herein we aim to review the role of apoptosis and genes associated with it in oral cancer development in order to aid in early diagnosis, prediction of malignant potential and evaluation of possible treatment targets in oral cancer. An internet-based search was done with key words apoptosis, genes, mutations, targets and analysis to extract 72 articles after considering inclusion and exclusion criteria. The knowledge of genetics and genomics of oral cancer is of utmost need in order to stop the rising prevalence of oral cancer. Translational approach and interventions at the early stage of oral cancer, targeted destruction of cancerous cells by silencing or promoting involved genes should be the ideal intervention.